Diverticular disease - Knowles, Charles (Henry Stewart Talks, 2011)
Diverticular disease, Increasing incidence of asymptomatic and complicated forms, Aetiology of disease and complications: low fibre, aging and obesity (complications), Medical management limited, surgical management complex and hazardous, Overall, high societal cost but little research investment
Archived at 2021/05/30